Antibacterial nanophotosensitizers in photodynamic therapy: An update. Issue 4 (April 2023) - Badran, Zahi; Rahman, Betul; De Bonfils, Paul; Nun, Pierrick; Coeffard, Vincent; Verron, Elise
Highlights: The WHO is seriously concerned about bacterial infections resistance in clinical medicine. Antibacterial Photodynamic Therapy (aPDT) represents a promising alternative to conventional antibacterial approaches. Increasing tissue penetration, water-solubility, target selectivity constitutes an exciting challenge to address. Smart solutions providing by nanotechnology increase efficacy of aPDT. Abstract : Bacterial infections constitute a major challenge of clinical medicine, particularly in specialties such as dermatology and dental medicine. Antiseptics and antibiotics are the main adjunctive therapies to anti-infective procedures in these specialties. However, antibacterial photodynamic therapy (PDT) has been introduced as a novel and promising alternative to conventional antibacterial approaches. PDT relies on the formation of reactive oxygen species (ROS) by a photosensitizer (PS) after activation by a specific light source. Nanotechnology was later introduced to enhance the antibacterial efficacy of PS during PDT. In this review, we describe the different nanoparticles (NPs) used in PDT and their properties. Recent in vivo data of NPs in antibacterial PDT in dermatology and dental medicine and their safety concerns are also reviewed.